Two Asymmetrically Mirrored Gap-Coupled Loop Antennas as a Compact Building Block for Eight-Antenna MIMO Array in the Future Smartphone - Wong, Kin-Lu; Tsai, Chih-Yu; Lu, Jun-Yu (IEEE transactions on antennas and propagation, 2017)
A compact two-antenna building block for forming the multiple-input multiple-output (MIMO) array in the mobile device such as the smartphone is presented. The building block has a planar structure of small size 7 × 10 mm 2 (about 0.08λ × 0.12λ) for operating at 3.5-GHz band (3.4-3.6 GHz), which is the recently identified frequency spectrum in World Radiocommunication Conference 2015 for future broadband mobile services. The building block is formed by two gap-coupled loop antennas having asymmetrically mirrored (AM) structures with respect to the system ground plane of the smartphone. The two AM antennas show good isolation thereof and their envelope correlation coefficient is much less than 0.1 in the operating band, showing very good independence of the two antennas in their far-field radiation characteristics. By using four such building blocks, an eight-antenna MIMO array at 3.5-GHz band in the smartphone is easily implemented. The channel capacity of the eight-antenna MIMO array in an 8 \× 8 MIMO system is calculated to be about 36 b/s/Hz with 20-dB signal-to-noise ratio. The measured channel capacity obtained using an 8 × 8 MIMO measurement setup is also presented, which generally agrees with the calculated results. The obtained eight-antenna MIMO array is promising for future or fifth-generation smartphone applications.